2004
DOI: 10.1176/appi.ajp.161.2.352
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Psychiatry Versus General Psychiatry Inpatient Treatment of the Elderly

Abstract: Geriatric psychiatry subspecialty inpatient care appears to be associated with distinct clinically relevant assessment and treatment advantages. Continuing geropsychiatric education of general psychiatrists is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
2
15
0
5
Order By: Relevance
“…We must bear in mind that dementia and delirium patients in the intensive care unit with constant nursing care can rapidly rip out the intravenous infusion, nasogastric probe, urinary catheter and the like. In such acute situations, a psychiatrist should try to communicate with bolesnikom na njegovoj razini ohrabrivajući pacijenta i pokušati ga orijentirati u prostoru, vremenu i prema drugim osobama (16,17).…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…We must bear in mind that dementia and delirium patients in the intensive care unit with constant nursing care can rapidly rip out the intravenous infusion, nasogastric probe, urinary catheter and the like. In such acute situations, a psychiatrist should try to communicate with bolesnikom na njegovoj razini ohrabrivajući pacijenta i pokušati ga orijentirati u prostoru, vremenu i prema drugim osobama (16,17).…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Važne su nam detaljne informacije o prijašnjim psihijatrijskim liječenjima, somatskim, kirurškim i drugim liječenjima, naročito ozljedama. Također treba obratiti pozornost na eventualno a demented patient at his level by encouraging the patient and trying to orient him in space, time and in relation with other people (16,17).…”
Section: Clinical Evaluationunclassified
“…Subspecialties such as geriatric psychiatry have been established in recognition of the distinct needs of older patients. Some studies have found that specialized care for elderly patients offer clinical advantages 1,2 . At the same time, psychiatric problems have been reported in elderly patients hospitalized in psychiatric units, much as has been noted in younger patients 3 …”
Section: Introductionmentioning
confidence: 99%
“…Dabei liegen Hinweise vor, dass psychia− trische Abteilungen allgemeinmedizinischen Ab− teilungen überlegen sind [14] und in der Gruppe der demenziellen Störungen eine zusätzliche Subspezialisierung in gerontopsychiatrischen Spezialeinheiten für die Patienten gewinnbrin− gend ist [15,16] In der GP−Gruppe wurden während einer antidepressiven Thera− pie sehr viel häufiger Laborwerte bestimmt als in der AP−Gruppe (t < 0,05, df = 73). Trizyklische Antidepressiva wurden in der AP− Gruppe signifikant häufiger verabreicht als in der GP−Gruppe (t < 0,01, df = 73).…”
unclassified
“…Besonders hervorzuheben ist, dass ein signifikant höherer Prozentsatz der in der GP behandelten Patienten eine umfassende somatische Untersuchung sowie Antidepressiva der neueren Generation erhielt. Andere neuere Studien kommen zu ähnlichen Ergebnissen [15,16]. Die fehlenden Unterschiede bei anderen Variablen könnten in der stationsübergreifenden Organisation der Behandlungssitua− tion begründet sein.…”
unclassified